2022
DOI: 10.1177/17562848221115312
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease and immune-mediated inflammatory diseases: looking at the less frequent associations

Abstract: Patients with inflammatory bowel disease (IBD) often have other immune-mediated inflammatory diseases (IMIDs), and the prevalence of any IMID is higher in IBD patients than in the general population. IBD and other IMIDs involve alterations in innate and adaptive immune responses. Their co-occurrence depends on shared immune and inflammatory processes, pathogenic mechanisms, and genetic and environmental risk factors, including drugs, especially tumor necrosis factor inhibitors. The more common IMIDs associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 172 publications
(266 reference statements)
0
13
0
Order By: Relevance
“…Autoimmune pancreatitis (AIP), first named by Yoshida et al in 1995, 3 is a immune-mediated inflammatory disease that is clinically characterized by obstructive jaundice, histologically characterized by dense lymphoplasmacytic infiltration and fibrosis, and therapeutically characterized by a dramatic response to corticosteroid therapy. 4 AIP can be classified based on histological and clinical profiling into two subtypes, ie, lymphoplasmacytic sclerosing pancreatitis (type 1 AIP) and idiopathic duct-centric pancreatitis (type 2 AIP). 5,6 Type 1 AIP is the pancreatic manifestation of systemic immunoglobulin G4 (IgG4) disease and occurs mostly in men in their 70s, while type 2 AIP is frequently seen in younger patients in their 50s and is often associated with IBD.…”
mentioning
confidence: 99%
“…Autoimmune pancreatitis (AIP), first named by Yoshida et al in 1995, 3 is a immune-mediated inflammatory disease that is clinically characterized by obstructive jaundice, histologically characterized by dense lymphoplasmacytic infiltration and fibrosis, and therapeutically characterized by a dramatic response to corticosteroid therapy. 4 AIP can be classified based on histological and clinical profiling into two subtypes, ie, lymphoplasmacytic sclerosing pancreatitis (type 1 AIP) and idiopathic duct-centric pancreatitis (type 2 AIP). 5,6 Type 1 AIP is the pancreatic manifestation of systemic immunoglobulin G4 (IgG4) disease and occurs mostly in men in their 70s, while type 2 AIP is frequently seen in younger patients in their 50s and is often associated with IBD.…”
mentioning
confidence: 99%
“…12,13 The common pathogeneses of UC and psoriasis are lifestyle factors, genetic overlap, gut microbial antigens, and shared immune and inflammatory processes. 14,15 Many treatments for psoriasis are also suitable for UC, such as infliximab 16 and ustekinumab. 17 Some studies have shown the opinion that inflammatory bowel disease (IBD) and psoriasis are both related to the immune response, which alter the microbiota of gut and skin after environmental triggers for genetically susceptible individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A nationwide population‐based matched cohort study in Korea showed that UC patients had an increased risk of psoriasis, with an incidence of 217.68 per 100 000 person‐years 12,13 . The common pathogeneses of UC and psoriasis are lifestyle factors, genetic overlap, gut microbial antigens, and shared immune and inflammatory processes 14,15 . Many treatments for psoriasis are also suitable for UC, such as infliximab 16 and ustekinumab 17 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there are increasing reports on the association between IBD and pancreatitis, but few has been mentioned about the causal relationship between the two [10][11][12][13][14][15]. IBD patients often have other immune-mediated in ammatory diseases, including autoimmune pancreatitis [10]. Autoimmune pancreatitis is more common in patients with IBD than in the general population [10,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…IBD patients often have other immune-mediated in ammatory diseases, including autoimmune pancreatitis [10]. Autoimmune pancreatitis is more common in patients with IBD than in the general population [10,16,17]. IBD and AIPrelated AP were accepted by the general public, but the pathophysiology of IBD and AP/CP is still controversial.…”
Section: Introductionmentioning
confidence: 99%